STUDI TENTANG DESAIN, TEKNIK PENGERJAAN DAN PEWARNAAN SABLON PADA KADAI TANGEKELEK - NUR IBRA ARAFA, Yofita Sandra, S.Pd., M.Pd. (Serupa The Journal of Art Education, 2019)
This study im to find out and examine more deeply how the design, workmanship techniques and tools and materials, screen printing coloring, then what colors are used in Tangkelek, whose information is not yet widely known to the public.This research included in qualitative descriptive research, the subject of this study included the owner of Tangkelek or founder of Tangkelek, and employees of Tangkelek. Furthermore, the object observed, namely screen printing on the Tangkelek Store itself. The method used to collect data is the method of observation, documentation, and interviews.The results of the study show that the tangelek design emphasizes the proverbial word of Minang, the technique used in Tangkelek screen printing still done manually by using monil and lighting, the colors found on the screen printing of these Tangkelek store vary from basic colors, red, blue, and yellow,Keywords: Design, Work Technique, and Screen Printing.